The efficiency of effective microorganism (EM) as catalyst in food waste composting using black soldier fly larvae - Ahmad Irfana Kabir; Basri Noor Ezlin Ahmad; Jalil Nurul ‘Ain Abdul; Amrul Nur Fardilla (E3S Web of Conferences, 2022)
Composting is sustainable alternative method which can be utilized to recycle organic wastes. In this research, black soldier fly (BSF) larvae and effective microorganisms (EM) were used together to compost organic waste. This study seeks to investigate the effectiveness of composting food waste using EM together with BSF larvae and to determine whether the growth of BSF larvae is affected by the presence of EM. 5 g of BSF larvae and 300 g of food wastes were put in four different containers with different concentration of EM (0-25%). The larvae were weighed throughout the 13-day experiment, and the changes in food waste volume were recorded to calculate the percentage of frass. Results showed that BSF larvae in the container which has the highest EM concentration (25% EM) produced the highest percentage of compost (89%). Meanwhile, there is a slight difference in the weight of larvae in all samples, where the weight ranges from 5.6 g to 6.5 g. In conclusion, the presence of EM can assist BSF larvae in accelerating the rate of food waste composting.